PROTECTION OF CHILD VICTIMS OF SEXUAL VIOLENCE FROM THE PERSPECTIVE OF PAPUAN CUSTOMARY LAW AS AN IMPLEMENTATION OF CONTEMPORARY VICTIMOLOGY PRINCIPLES - Salma Daeng Mamase; Siti Salma Kastela (Papua Law Review, 2026)
Sexual violence against children constitutes a grave violation of human rights with profound and long-lasting consequences for victims' physical, psychological, and social well-being. In Papua, the protection of child victims is shaped not only by the national legal system but also by customary law, which continues to play a significant role in regulating social relations and resolving disputes within Indigenous communities. While Papuan customary law emphasizes reconciliation, communal harmony, and customary compensation, these mechanisms do not always fully guarantee the rights, protection, and recovery of child victims as required under contemporary victimology principles. This study aims to examine the protection of child victims of sexual violence from the perspective of Papuan customary law and to analyze its compatibility with contemporary victimology principles as reflected in Law Number 35 of 2014 concerning Child Protection and Law Number 12 of 2022 concerning Sexual Violence Crimes. Employing normative legal research with statutory, conceptual, and customary law approaches, this study analyzes legal norms governing victim protection and their interaction with customary justice practices in Papua. The findings indicate that although customary law contributes to maintaining social cohesion and restoring community harmony, greater attention is needed to ensure child victims' rights to protection, participation, psychological recovery, restitution, and rehabilitation. The study concludes that integrating contemporary victimology principles into Papuan customary law can strengthen child protection while preserving Indigenous legal values and cultural identity. Such integration requires greater collaboration between customary institutions and state law enforcement agencies to establish a culturally responsive and victim-oriented justice system.